1989
DOI: 10.1002/bjs.1800760119
|View full text |Cite
|
Sign up to set email alerts
|

Paget's disease of the anus: A clinicopathological study

Abstract: Paget's disease of the anus is a rare disorder of controversial origin and is frequently associated with malignancy. We studied eight patients and carried out immunohistochemical studies to determine whether particular functional profiles might be indicators of a malignant association. One patient presented with synchronous carcinoma and two developed carcinomas 3 and 10 years after excision of Paget's disease. Five patients underwent wide local excision and have not developed cancer (median follow-up 6 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 22 publications
0
45
1
Order By: Relevance
“…For PPD patients without invasive malignancy, WLE has usually been considered an adequate treatment (3,5,17), but our present data show a high rate of recurrence. Four of eight patients treated by WLE developed local recurrences, one of which was invasive.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…For PPD patients without invasive malignancy, WLE has usually been considered an adequate treatment (3,5,17), but our present data show a high rate of recurrence. Four of eight patients treated by WLE developed local recurrences, one of which was invasive.…”
Section: Discussioncontrasting
confidence: 52%
“…Recent studies suggest that certain molecular markers in Paget cells may have implications for clinical management and prognosis (17,18). The tumor suppressor gene p53 has been found to be the most commonly mutated gene in human malignancy (19,20).…”
mentioning
confidence: 99%
“…These cases, different from primary vulvar Paget disease, typically express cytokeratin 20 and, at the same time, immunohistochemical reactions for GCDFP15 are negative [57,[60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Diagnosis ofExtran the same antibody. Armitage et al 12 also found a few cases of EPD that were negative for CAM 5.2. While this antigen is expressed in most cases of EPD, a minority of cases may be negative, and these are not associated with specific clinical features.…”
Section: Discussionmentioning
confidence: 99%